High‐resolution probing of inner core structure with seismic interferometry. Issue 24 (23rd December 2015) - Huang, Hsin‐Hua; Lin, Fan‐Chi; Tsai, Victor C.; Koper, Keith D.
Abstract: Increasing complexity of Earth's inner core has been revealed in recent decades as the global distribution of seismic stations has improved. The uneven distribution of earthquakes, however, still causes a biased geographical sampling of the inner core. Recent developments in seismic interferometry, which allow for the retrieval of core‐sensitive body waves propagating between two receivers, can significantly improve ray path coverage of the inner core. In this study, we apply such earthquake coda interferometry to 1846 USArray stations deployed across the U.S. from 2004 through 2013. Clear inner core phases PKIKP 2 and PKIIKP 2 are observed across the entire array. Spatial analysis of the differential travel time residuals between the two phases reveals significant short‐wavelength variation and implies the existence of strong structural variability in the deep Earth. A linear N‐S trending anomaly across the middle of the U.S. may reflect an asymmetric quasi‐hemispherical structure deep within the inner core with boundaries of 99°W and 88°E. Key Points: Clear core phases are extracted across the entire USArray using earthquake coda interferometry A strong N‐S trending travel time anomaly is observed across the central U.S. An inner core hemispherical model with boundaries at longitude 99 W and 88E is proposed